Nutrients retention of a series of small dam-impacted urban rivers in northern China. Issue 3 (June 2022) - Kumwimba, Mathieu Nsenga; Bao, Linlin; Jie, Zhishi; Li, Xuyong; Huang, Jinlou; wang, Wei; Li, Xinzhu; Su, Jingjun; Muyembe, Diana Kavidia; Guide, Awoke; Dzakpasu, Mawuli
Abstract: How a series of small rubber dams distributed within urban watersheds impact nutrients transport remains less investigated. To fill this research gap, this study assesses the composition of nitrogen (N) and phosphorus (P) and their retention in five urban river segments across the Qingshui-Yanghe rivers, China from March 2019 to September 2021. The upstream and downstream of the Qingshui river (QR-up and QR-city) were enriched with dissolved N and particulate P, suggesting a greater P contribution of agricultural origin. NH4 -N concentrations were lower upstream but increased downstream of the Yanghe river due to the direct discharge of sewage and other human activities. N and P concentrations varied along the urban river and were relatively low at QR-city. A total of 159.2 and 8.4 metric tons/yr, corresponding to 63% and 70% of the TN and TP loading, were trapped within QR-up and QR-city, of which the dissolved N and particulate P load retention accounted for 58% and 78%. N and P retention rates within the river segments sharply decreased from 97 to –320% and were mainly sequestered in the upstream river segments (QR-up- QR-city). The retention rate of nitrate (78%) and dissolved reactive P (67%) were higher than that of TPN (9.75%) and TPP (78%) because of biological assimilation. Further, with retention rates of −320%, the upstream river segments were a net source of dissolved organic P. These results confirm that the small dams have an important nutrient retention function that is highly variable on a spatiotemporal scale similarly to large-scale reservoirs. Due to the cumulative influence of sewage discharge downstream of the Yanghe River, the nutrient load retention is significantly higher than that in the Qingshui river segments. The variations in hydrological regimes due to seasonal events and small dam regulation have a substantial impact on nutrient retention, resulting in higher loads retention in the flood period than in other periods. Overall, the results suggest that management plans must not only focus on decreasing nutrient export from the mountainous area of the Qingshui river basin but also on sewage outfalls and enhancing the hydrodynamic status of the dammed rivers with respect to eutrophication. Graphical Abstract: ga1 Highlights: The role of small dams in retaining and altering riverine nutrient loading was estimated via mass balance approach. The TP and TN levels remained relatively high in some river segments. 63.1% (159.2 metric tons/yr) of TN and 70.4 ( 8.4 t/yr) 8.4 t/yr) of TP were trapped within rubber dams between 2019 and 2021. Site upstream of the dammed river had higher N and P retention. Decreasing nutrient export from watershed and enhancing hydrodynamic states of the dammed system is required to prevent eutrophication.